Daily profile of glut1 and glut4 expression in tissues inside and outside the blood-brain barrier in control and streptozotocin-treated rats - Soltésová, D; Veselá, A; Mravec, B; Herichová, I (Physiological research, 2013)
Glucose is molecule usually studied in relation to metabolism. Except for this traditional view, it is known that under certain conditions glucose can serve as a signal molecule for the circadian system. The circadian system is entrained by relevant synchronizing cues that can be tissue-dependent. Central oscillator is synchronized mainly by light-dark cycle, while peripheral oscillators can be entrained by food intake. Glucose transport in the organism is controlled by insulin dependent and independent mechanism. Therefore, we employed streptozotocin-induced diabetes to elucidate the influence of metabolic changes on glucose transporter (glut1, glut4) 24-h expression profile in peripheral oscillators in tissues, inside (frontal cortex, cerebellum) and outside (heart) the blood-brain barrier. Diabetes was induced by streptozotocin injection. Seventeen days later, sampling was performed during a 24-h cycle. Gene expression was measured using real-time PCR. We observed down-regulation of glut1 and glut4 expression in the heart of diabetic rats. The expression of glut1 and glut4 in brain areas was not down-regulated, however, we observed trend to phase advance in glut1 expression in the cerebellum. These results may indicate higher glucose levels in diabetic brain, which might influence regulation of clock gene expression in different manner in brain compared to periphery.
Keywords: Circadian Rhythm; Tissue Distribution; cirkadiánní hodiny; glukosa; Rats; Blood-Brain Barrier; Glucose Transporter Type 4; Streptozocin; cirkadiánní rytmus; přenašeč glukosy typ 1; Rats, Wistar; mužské pohlaví; Circadian Clocks; krysa rodu Rattus; experimentální diabetes mellitus; zvířata; tkáňová distribuce; přenašeč glukosy typ 4; Diabetes Mellitus, Experimental; potkani Wistar; streptozocin; hematoencefalická bariéra; Glucose Transporter Type 1; Glucose; Male; Animals